Board Diversity and Human Capital Reporting of Selected Firms: Evidence from Nigeria - Olaoye, Clement Olatunji; Oladele, Mary Ayoola (The Journal of Accounting and Management, 2024)
This study examined the influence of board diversity on human capital reporting (HCR) in selected firms, focusing on the impact of board gender composition, audit committee gender composition, foreign directorship and the educational qualifications of board members. Utilizing a robust dataset and employing quantitative methods. The research finds that approximately 20.56% of the variation in HCR can be explained by the independent variables included in the model. The study highlights a statistically significant relationship, supported by an F-statistic of 18.76 (p-value = 0.0000), indicating the relevance of diverse governance structures in promoting transparency and accountability in human capital reporting. Empirical evidence from recent literature reinforces these findings, demonstrating that organizations with diverse boards are more likely to engage in comprehensive and transparent human capital disclosures. The theoretical framework applied underscores the critical role of board diversity in enhancing corporate governance and stakeholder engagement. The study concludes that fostering diversity within boards and audit committees can lead to improved HCR, ultimately contributing to better organizational performance and accountability. Recommendations for practice include promoting gender diversity and educational qualifications on boards to enhance human capital reporting and stakeholder communication.